Mycena dollyae—a new species from tropical India - Manakkat, Manjulakshmi M.; Latha, K. P. Deepna; Raj, K. N. Anil (Phytotaxa, 2026)
Mycena dollyae sp. nov. is described from Kerala State, India, based on both morphological characteristics and molecular phylogenetic analyses. It is characterized by a small, corticolous habitat, a slightly depressed, brownish gray pileus with a pruinose surface, narrowly adnate to adnate and pseudocollariate lamellae, ellipsoid to subglobose and amyloid basidiospores, a lamella-edge with dimorphic cheilocystidia and a cutis-type pileipellis composed of cystidioid hyphal ends with simple or cylindrical excrescences. Morphologically, these features suggest placement within Mycena section Supinae. However, based on molecular phylogenetic analyses of the internal transcribed spacer (nrITS) and large subunit (nrLSU) regions of the ribosomal RNA gene, the new species could not be placed in any of the sections proposed for this genus. Instead, it clustered with a few Mycena species that have not so far been assigned to any of the known sections. A detailed description with photographs and line drawings of both the basidiomata and the microscopic structures, comparisons with phenetically similar and phylogenetically related species, and a phylogram illustrating the placement of the new species are provided.